The effects of menstrual phase on orthodontic pain following initial archwire engagement. (8th February 2017) - Long, H; Gao, M; Zhu, Y; Liu, H; Zhou, Y; Liao, L; Lai, W
Abstract : Objectives: To explore the effects of menstrual cycle on orthodontic pain following initial archwire engagement. Methods: Female participants with regular menstrual cycles were recruited and assigned into follicular group or luteal group. Demographical and baseline variables were collected: age, education, menstrual duration, anxiety, oral health impact profile‐14 (OHIP‐14), and index of complexity outcome and need (ICON). Following initial archwire engagement, orthodontic pain was determined through visual analogue scale (VAS) on 1st day, 2nd day, and 3rd day. Demographical and baseline variables were compared between the two groups. Two‐way repeated‐measuresanova was used to examine the effects of menstrual phase, time, and their interactions on orthodontic pain. Multivariate linear regression was employed to examine the independent effect of each variable on orthodontic pain. Results: Finally, 37 and 39 were assigned to the follicular and luteal groups, respectively, with balanced demographical and baseline data. Orthodontic pain was significantly affected by menstrual phase and time (both P < 0.001), but there was no interaction ( P > 0.05). Moreover, orthodontic pain was independently predicted by menstrual phase, OHIP, education level, and anxiety (all P < 0.05). Conclusion: We suggest that practitioners arrange female patients to receive initial archwire engagement during their follicular phases to relieve orthodontic pain.